Preterm infants with positive conjunctival swab culture: risk factors and association with late-onset sepsis–a retrospective cohort study - Gad, Ashraf; Khalil, Amr; Halil, Muhammed; Chandra, Prem; Soliman, Aly; Rahman E’mar, Abdel; Ibrahim, Marwa; Al Khzzam, Fadi; AlHendawi, Talal; Hamed, Manal; Bayoumi, Mohammad A. A.; Petkar, Hawabibee (Frontiers in Pediatrics, 2023)
Introduction: Purulent conjunctival discharge in hospitalized preterm infants may indicate conjunctivitis and warrant treatment. The purpose of this study was to examine the relationship between positive conjunctival swab (CS) culture and Sepsis in preterm infants. Methods: A retrospective cohort study was conducted to determine the relationship between positive CS culture growth results (CSP) obtained in preterm infants ≤ 34 weeks' gestation and the development of LOS within 120 hours of obtaining CS compared with those who had negative CS culture results (CSN). Electronic medical records were reviewed from January 2015 until December 2019 for preterm infants with positive conjunctival culture swabs. Results: Of the 234 CS cultures obtained during the study period, 145 (61.9%) were CSP compared to 89 (38.1%) CSN cultures. Gram-negative organisms accounted for 70% of all CSP cultures, with the remaining 30% being Gram-positive. Patients with CSP were smaller, younger, had lower 1-minute APGAR scores, and required respiratory support more frequently than those with CSN. Infants with CSP received antibiotics for longer periods, both topically and systemically. Infants who developed sepsis were more likely to require invasive ventilation (adjusted odds ratio, 33.5; 95% CI, 2.52-446.5, p=0.008). The incidence of LOS between the two groups was similar, with 6.2% observed in the CSP group compared to 3.4% in the CSN group (p=0.543). Similarly, the rates of bacteremia were similar in both groups. Of the CSP patients who were presented with bacteremia, four out of seven (57%) exhibited bacteremia caused by the same organism. Similarly, within the entire cohort, respiratory cultures were performed on nine intubated patients within two weeks of obtaining CS cultures. Of these, in the CSP group, five out of six (83%) showed an organism identical to that found in the CS cultures. Conclusion: The study found a significant proportion of positive CS cultures in preterm infants, with distinct patient characteristics and treatment compared to negative cultures. While the incidence of Sepsis wasn't significantly different between the two groups, some CSP patients demonstrated bacteremia with the same organism, suggesting a possible connection between conjunctival or respiratory colonization and bacteremia.